A Comprehensive Approach to Revealed Preference Theory - Nishimura, Hiroki; Ok, Efe A.; Quah, John K.-H. (American Economic Review, 2017)
We develop a version of Afriat's theorem that is applicable in a variety of choice environments beyond the setting of classical consumer theory. This allows us to devise tests for rationalizability in environments where the set of alternatives is not the positive orthant of a Euclidean space and where the rationalizing utility function is required to satisfy properties appropriate to that environment. We show that our results are applicable, amongst others, to choice data on lotteries, contingent consumption, and intertemporal consumption. (JEL D11, D81)